2022
DOI: 10.1186/s12913-022-07914-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the implementation and impact of navigator-supported remote symptom monitoring and management: a protocol for a hybrid type 2 clinical trial

Abstract: Background Symptoms in patients with advanced cancer are often inadequately captured during encounters with the healthcare team. Emerging evidence demonstrates that weekly electronic home-based patient-reported symptom monitoring with automated alerts to clinicians reduces healthcare utilization, improves health-related quality of life, and lengthens survival. However, oncology practices have lagged in adopting remote symptom monitoring into routine practice, where specific patient populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…34,56,66 Other groups have since published study protocols including prospective evaluation of implementation as part of hybrid implementation-effectiveness studies. 67,68 The study captured the perspectives of under-studied stakeholders, including caregivers, clinic administrators, pharmacists, and IT specialists, which helped identify novel barriers and facilitators. Early consultation with stakeholders may also enhance their engagement with future implementation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…34,56,66 Other groups have since published study protocols including prospective evaluation of implementation as part of hybrid implementation-effectiveness studies. 67,68 The study captured the perspectives of under-studied stakeholders, including caregivers, clinic administrators, pharmacists, and IT specialists, which helped identify novel barriers and facilitators. Early consultation with stakeholders may also enhance their engagement with future implementation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms through which remote symptom monitoring improves patient and caregiver outcomes are starting to be determined through research. This includes linkages between patient reporting, clinician actions and subsequent improvements in patient outcomes (e.g., earlier detection, improved symptom management, reduced symptom burden and reduced distress) [35]. However, to date, research depicting how remote symptom monitoring leads to changes in outcomes has been based on research evidence from high-resource settings [35].…”
Section: Remote Symptom Monitoring For Palliative Cancer Care In Sub-...mentioning
confidence: 99%
“…The University of Alabama at Birmingham (UAB) has made ePROs standard of care for patients with cancer and is one of the first to enroll patients with early and advanced stages. 12 Additionally, patients with breast cancer are ideal for initial evaluation due to the clear differentiation between early stage breast cancer (EBC) and advanced stage breast cancer. 13 Thus, this study aims to evaluate the association between patients' severity of patient-reported symptom alerts and the time to response by the health care team.…”
Section: Introductionmentioning
confidence: 99%